Application of Ecobrick as a Garden Hardscape Material - Hendra Fahruddin Siregar; Rahmadhani Fitri (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
Ecobricks are solid plastic bottles filled with non-biological waste to make reusable building blocks. Eco-bricks is a collaboration-based technology that provides solid waste solutions at no cost to individuals, households, schools and communities. Also known as Bottle Brick or Ecoladrillo. The service method is by conducting an ecobrick workshop then making ecobrick chairs and educating about plastic waste. Ecobricks can be a hardscape material and as an artificial resource. The use of ecobricks is expected to be a change in the use of resources. The production process can be modified to allow the substitution of useless materials to be utilized.